2019
DOI: 10.24843/eja.2019.v26.i01.p20
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Love of Money, Machiavellian, Idealisme dan Religiusitas pada Persepsi Etis Mahasiswa Akuntansi

Abstract: ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pengaruh love of money, machiavellian, idealisme dan religiusitas pada persepsi etis mahasiswa akuntansi. Populasi penelitian ini adalah mahasiswa S1 program studi akuntansi non reguler angkatan 2015 Fakultas Ekonomi Universitas Udayana Bali yang berjumlah 148 orang, sampel yang diambil berjumlah 108 orang. Uji coba instrumen dilakukan dengan uji validitas dan uji reliabilitas. Sebelum dilakukan analisis data, terlebih dahulu dilakukan uji prasyarat ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…In line with Devi & Ramantha (2017) research, which states that Machiavellian has a positive and significant effect on auditor's dysfunctional behavior. However, research conducted by Nikara & Mimba (2019) states that Machiavellian damages the ethical perceptions of accounting students.…”
Section: Introductionmentioning
confidence: 99%
“…In line with Devi & Ramantha (2017) research, which states that Machiavellian has a positive and significant effect on auditor's dysfunctional behavior. However, research conducted by Nikara & Mimba (2019) states that Machiavellian damages the ethical perceptions of accounting students.…”
Section: Introductionmentioning
confidence: 99%
“…Selain menggunakan keenam elemen dari fraud hexagon, dalam penelitian ini juga menambahkan variabel lain seperti machiavellian dan love of money. Machiavellian adalah sebuah desain perilaku sosial yang mengaitkan seseorang untuk menghasut orang lain agar menentang kepentingan umum demi memperoleh keuntungan pribadi (Nikara & Mimba, 2019). Sedangkan arti dari love of money merupakan perilaku seseorang yang terlalu cinta terhadap uang dan memandang uang sebagai hal yang terpenting dalam hidupnya (Husnurrosyidah, 2019).…”
unclassified
“…In the category of interpersonal relationships, negative behaviors include inciting colleagues to violate company rules, frequently ordering colleagues, initiating personal conversations during working hours, and being manipulative or blaming others for their mistakes. Nikara & Mimba (2019) revealed that Machiavellian individuals incite their colleagues to oppose common interests, benefiting their personal interests. Examples show that Machiavellian individuals have no hesitation in inciting colleagues to violate company rules and initiating personal conversations during working hours.…”
Section: Results Dan Discussionmentioning
confidence: 99%